PENGEMBANGAN KURIKULUM LEMBAGA PENGAJIAN ANAK (LPA) DI KOTA KULON - ahsan hasbulah (IAIN Purwokerto, 2015)
Abstract: This study shows that the implementation of the pengajian Anak Institute (LPA-Children's Religious Teaching Institute) in Kota Kulon have resulted that students have the ability to read the letters of the Koran and ability to practice five prayers etc (wudlu, rote short surah, and prayer). Subject matter provided in the LPA Kota Kulon is material relating to read the letters of the Koran and the implementation of the five daily prayers: material about the purification ritual, prayer readings, prayer movements memorizing short letter (Juz Amma), and daily prayer. In leaming to read the letters of the Quran, the main source of the material is lqro Book and the Koran. These LPA using a system of private' or khalagoh system (individual system) to study Qur'an, uses classical system for the Islamic education generally. The method used in leaming to read the letters of the Quran using methods Igro and only a few were still using traditional methods (methods Alif Ba Ta). The method used in Islamic education, among others: methods of lectures, assignments, drill (habituation), and the method of demonstration. This type of evaluation to assess the results of leaming are generally formative (assessment at the end of a material/sub-subject/subjects) and conducted orally (Oral Test). There are several LPA which doing formative evaluation, sub-summative and summative and put it into a report book leaming progress of students (book report cards). Keywords: Curriculum, Children's Religious Teaching Institute.